Assessment of the performance of waste stabilization pond at the Cape Coast Teaching Hospital in Ghana - Tornyi, Janet Mawunyo (University of Cape Coast, 2017)
In developing countries, hospital wastewater management is an issue of major concern. The purpose of the study was to evaluate the performance of the waste stabilization pond at the Cape Coast Teaching Hospital in Ghana. Wastewater samples were taken from the raw sewage (anaerobic pond) after screening. The process was repeated in both the facultative and maturation ponds, sequentially. Fifty four samples representing 18 samples each from the three stages of the waste stabilization treatment were analysed to evaluate the efficiency of the ponds over a period of six months. The selected parameters were analysed based on a well-established protocols. Descriptive and inferential statistics were used to determine the distribution and relationships among wastewater parameters measured in the stabilization ponds. The results showed that the final effluent values obtained for most of the parameters were within the acceptable limits of the Ghana Environmental Protection Agency. However, conductivity, TSS, turbidity, nitrate, phosphorus, magnesium and mercury levels were not compliant. The efficiency of the WSP for turbidity was 56.78%, TSS 71.96%, BOD 64.78%, magnesium 3.55%, total coliforms 34.48%, E.coli 53.53%, Iron 50.60%, manganese 75.40%, and cadmium 47.83%. The rest of the parameters exhibited negative values. Based on the low efficiency removal of some of the parameters, the effluent should be treated to prevent any possible pollution in the environment.
xv, 146p.: ill.
Keywords: Wastewater management; Stabilization pond; pond; Treatment